Free Delivery Serving and Religious Issue to Enhance Local Retail Competitiveness Facing National Minimarket - Andayani Andayani; Ahmad Nuh; Tantri Yanuar Rahmat Syah; Rhian Indradewa; Diana Fajarwati (Penerbit Kemala Indonesia, 2020)
This paper is discussing about the strategy of a retail store business model that uses a delivery and sale of service eat products while a concept aims to efficient, faster, and customer-oriented practices. The development connection of IT solutions in urban logistics operations, supply chain efficiency, and new business model will be delivered as a Service i.e. service-oriented delivery and evolution business processes with adjust the expectations and customers’ needs in lifestyle development of urban communities at Indonesia. Thus, in this study also concludes that religious issues related to brand and company names have the power to build a retail store business especially minimarket with STP methods